The neglected 95% revisited: Is American psychology becoming less American? - Thalmayer, Amber Gayle; Toscanelli, Cecilia; Arnett, Jeffrey Jensen (The American psychologist, 2021)
The field of psychology prides itself on being a data-driven science. In 2008, however, Arnett brought to light a major weakness in the evidence on which models, measures, and theories in psychology rest. He demonstrated that the most prominent journals in six subdisciplines of psychology focused almost exclusively (over 70% of samples and authors) on a cultural context, the United States, shared by only 5% of the world's population. How can psychologists trust that these models and results generalize to all humans, if the evidence comes from a small and unrepresentative portion of the global population? Arnett's analysis, cited over 1,300 times since its publication, appears to have galvanized researchers to think more globally. Social scientists from the United States have increasingly sought ways to collaborate with colleagues abroad. Ten years later, an analysis of the same 6 journals for the period of 2014 to 2018 indicates that the authors and samples are now on average a little over 60% American based. The change is mainly due to an increase in authorship and samples from other English-speaking and Western European countries. Thus, it might be said that 11% of the world's population is now represented in these top psychology journals, but that 89% of the world's population continues to be neglected. Majority world authors and samples (4-5%) are still sorely lacking from the evidence base. Psychology still has a long way to go to become a science truly representative of human beings. Several specific recommendations are discussed. (PsycInfo Database Record (c) 2021 APA, all rights reserved).